Energy Efficiency Analysis Through Solar Power Generation System as a New Renewable Energy Source at PT. Bunga Flour Mils Medan - Muhammad Rizki Alfurqon; Muhammad Erpandi Dalimunthe; Rahmaniar Rahmaniar (Sean Institute, 2025)
The development of the industrial revolution 4.0 has led to a surge in energy demand that continues to increase, driving the need for the implementation of new renewable energy sources, one of which is the Solar Power Plant (PLTS). This study aims to analyze the energy efficiency generated by the PLTS system at PT. Bunga Flour Mills Medan as an alternative solution in reducing dependence on conventional energy. The research method includes measuring output power, energy conversion efficiency, and analyzing the costs and benefits of implementing PLTS. The results of the study indicate that the implemented PLTS system has a fairly high efficiency with a significant contribution to saving the company's electricity consumption. In addition, the use of PLTS also has a positive impact on reducing carbon emissions and electricity operational costs in the long term. Thus, PLTS can be an effective and sustainable solution in supporting energy efficiency in the industrial sector.